High-speed low-power voltage-programmed driving scheme for AMOLED displays - 夏兴衡 吴为敬 宋小峰 李冠明 周雷 张立荣 徐苗 王磊 彭俊彪 (Journal of semiconductors, 2015)
A new voltage-programmed driving scheme named the mixed parallel addressing scheme is presented for AMOLED displays, in which one compensation interval can be divided into the first compensation frame and the consequent N – 1 post-compensation frames without periods of initialization and threshold voltage detection.The proposed driving scheme has the advantages of both high speed and low driving power due to the mixture of the pipeline technology and the threshold voltage one-time detection technology. Corresponding to the proposed driving scheme, we also propose a new voltage-programmed compensation pixel circuit, which consists of five TFTs and two capacitors（5T2C）. In–Zn–O thin-film transistors（IZO TFTs） are used to build the proposed 5T2 C pixel circuit. It is shown that the non-uniformity of the proposed pixel circuit is considerably reduced compared with that of the conventional 2T1C pixel circuit. The number of frames（N） preserved in the proposed driving scheme are measured and can be up to 35 with the variation of the OLED current remaining in an acceptable range.Moreover, the proposed voltage-programmed driving scheme can be more valuable for an AMOLED display with high resolution, and may also be applied to other compensation pixel circuits.